Tooth Structure and Replacement of the Triassic Keichousaurus (Sauropterygia, Reptilia) From South China - Liao, Jun-ling; Lan, Tian; Xu, Guang-hui; Li, Ji; Qin, Yan-jiao; Zhao, Ming-sheng; Li, Yu-lan; Wang, Yue (Frontiers in Ecology and Evolution, 2021)
The small-sized sauropterygian Keichousaurus hui was one of the most abundant marine reptiles from the Triassic Yangtze Sea in South China. Although Keichousaurus has been studied in many aspects, including the osteology, ontogeny, sexual dimorphism, and reproduction, the dentition of this marine reptile was only briefly described in external morphology. In this study, we provide new information on Keichousaurus tooth implantation, histology, and replacement based on a detailed examination of well-preserved specimens collected in the past decades. The tooth histology has been investigated for the first time by analyzing cross-sections of premaxillary teeth and the tooth attachment and implantation have been further revealed by X-ray computed microtomography. We refer the tooth replacement of Keichousaurus to the iguanid replacement type on the basis of the observed invasion of small replacement tooth into the pulp cavity of the functional tooth. Given the resemblance to other extinct and modern piscivorous predators in the morphology and structure of teeth, Keichousaurus might mainly feed on small or juvenile fishes and some relatively soft-bodied invertebrates (e.g., mysidacean shrimps) from the same ecosystem.